The last man [compact disc, unabridged] - Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2012)
"On the surface it appears as if top CIA agent Joe Rickman has been kidnapped, but Mitch Rapp knows enough about his colleague to believe that something else is going on, and that something could be far worse. Assigned to find his old friend, Rapp must make his way through a tangled and dangerous web that is set against the turbulent backdrop of war-torn Afghanistan"--Container.